DNA barcoding uncovers cryptic diversity in 50% of deep-sea Antarctic polychaetes. Issue 11 (November 2016) - Brasier, Madeleine J.; Wiklund, Helena; Neal, Lenka; Jeffreys, Rachel; Linse, Katrin; Ruhl, Henry; Glover, Adrian G.
Abstract : The Antarctic marine environment is a diverse ecosystem currently experiencing some of the fastest rates of climatic change. The documentation and management of these changes requires accurate estimates of species diversity. Recently, there has been an increased recognition of the abundance and importance of cryptic species, i.e. those that are morphologically identical but genetically distinct. This article presents the largest genetic investigation into the prevalence of cryptic polychaete species within the deep Antarctic benthos to date. We uncover cryptic diversity in 50% of the 15 morphospecies targeted through the comparison of mitochondrial DNA sequences, as well as 10 previously overlooked morphospecies, increasing the total species richness in the sample by 233%. Our ability to describe universal rules for the detection of cryptic species within polychaetes, or normalization to expected number of species based on genetic data is prevented by taxon-specific differences in phylogenetic outputs and genetic variation between and within potential cryptic species. These data provide the foundation for biogeographic and functional analysis that will provide insight into the drivers of species diversity and its role in ecosystem function.